Hubungan motivasi kerja dengan kinerja karyawan di ruang operasi dan pemeliharaan (op) - Hertanto, Ridho Bagas; Rukmana, Nova Mega; Novariana, Nana (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2025)
Background: There has been a decline in the effectiveness of public services in the irrigation sector, characterized by delayed technical responses and suboptimal irrigation canal maintenance. The actual situation indicates a decline in employee performance triggered by a lack of motivation, incentives, training, and weak supervision. Purpose: To analyze the relationship between work motivation and employee performance at the Adipuro Irrigation Regional Technical Implementation Unit (UPTD), Central Lampung Regency. Method: A quantitative approach with a cross-sectional design. The population and sample were all 30 employees in the Operations and Maintenance (OP) division at the Adipuro Irrigation UPTD. Data were collected through questionnaires and analyzed using descriptive and inferential statistics, with the Chi-Square Test as the primary method for testing hypotheses. Results: The majority of respondents (60% or 18 people) reported a "Poor" level of work motivation. Meanwhile, employee performance was evenly distributed, with 50% of respondents reporting "Good" performance and 50% reporting "Poor" performance. Conclusion: There is a significant relationship between work motivation and the performance of operations and maintenance (OP) employees (p < 0.05). This means that the better the work motivation, the better the employee's performance level.   Keywords: Employee Performance; Work Motivation.   Pendahuluan: Terjadinya penurunan efektivitas pelayanan publik di sektor pengairan, yang ditandai dengan keterlambatan respons teknis dan pemeliharaan saluran irigasi yang tidak optimal. Kondisi faktual menunjukkan adanya indikasi penurunan kinerja pegawai yang dipicu oleh kurangnya motivasi, insentif, pelatihan, serta lemahnya pengawasan. Tujuan: Untuk menganalisis hubungan antara motivasi kerja dengan kinerja karyawan di Unit Pelaksana Teknis Daerah (UPTD) Pengairan Adipuro, Kabupaten Lampung Tengah. Metode: Pendekatan kuantitatif dengan desain cross-sectional. Populasi sekaligus sampel penelitian adalah seluruh karyawan bidang Operasi dan Pemeliharaan (OP) di UPTD Pengairan Adipuro yang berjumlah 30 orang. Data dikumpulkan melalui kuesioner dan dianalisis menggunakan statistik deskriptif dan inferensial, dengan Uji Chi-Square sebagai metode utama untuk menguji hipotesis. Hasil: Mayoritas responden (60% atau 18 orang) memiliki tingkat motivasi kerja yang "Kurang Baik". Sementara itu, kinerja karyawan terdistribusi merata, di mana 50% responden menunjukkan kinerja "Baik" dan 50% "Kurang Baik". Simpulan: Terdapat hubungan yang signifikan antara motivasi kerja dengan  kinerja karyawan operasi dan pemeliharaan (op) (p < 0.05). Artinya, semakin baik motivasi kerja semakin baik tingkat kinerja karyawan.   Kata Kunci: Kinerja Karyawan; Motivasi Kerja.